2023
DOI: 10.1080/0886022x.2023.2202264
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key biomarkers of the glomerulus in focal segmental glomerulosclerosis and their relationship with immune cell infiltration based on WGCNA and the LASSO algorithm

Abstract: Objective The aim of our study was to identify key biomarkers of glomeruli in focal glomerulosclerosis (FSGS) and analyze their relationship with the infiltration of immune cells. Methods The expression profiles (GSE108109 and GSE200828) were obtained from the GEO database. The differentially expressed genes (DEGs) were filtered and analyzed by gene set enrichment analysis (GSEA). MCODE module was constructed. Weighted gene coexpression network analysis (WGCNA) was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Finally, we jointly analyzed the relevant potential biomarkers and ceRNA networks in the glomeruli of FSGS [ 19 , 64–66 ] according to the above key biomarkers of the FSGS tubulointerstitium and found that there was a relationship among the biomarkers. First, a total of 12 biomarkers identified by bioinformatics were summarized in the FSGS glomerular microarray dataset (FN1, EGF, TTR, BMP-2, COL4A1, C3AR1, CCR1, CX3CL1, MTNR1A, P2RY13, TGFB1, and NOTCH1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we jointly analyzed the relevant potential biomarkers and ceRNA networks in the glomeruli of FSGS [ 19 , 64–66 ] according to the above key biomarkers of the FSGS tubulointerstitium and found that there was a relationship among the biomarkers. First, a total of 12 biomarkers identified by bioinformatics were summarized in the FSGS glomerular microarray dataset (FN1, EGF, TTR, BMP-2, COL4A1, C3AR1, CCR1, CX3CL1, MTNR1A, P2RY13, TGFB1, and NOTCH1).…”
Section: Discussionmentioning
confidence: 99%
“…To fully understand the regulatory mechanisms of the biomarkers, a detailed analysis of the transcription factors and ceRNAs of the key biomarker PPARGC1A in the FSGS tubulointerstitium was conducted, and the results of previous studies on FSGS glomeruli [ 19 , 64 ] were compared and analyzed. First, regarding the transcription factors, there was no intersecting gene among the three, and the intersecting gene between the glomeruli of the two was determined to be RUNX3.…”
Section: Discussionmentioning
confidence: 99%